DETERMINANTS OF MONETARY VARIABLES AND PHILIPS CURVE TESTING OF INFLATION IN ASIAN COUNTRIES - Niken Hesty Wulandari; Muhammad Khoirul Fuddin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study examined the impact of monetary variables on inflation and determined the validity of the Phillips curve in the Asian context. It applied a quantitative methodology with a descriptive orientation. The data source utilized was the World Bank from 2013 to 2022, and the analysis approach employed was panel data regression. The research findings indicate that the money supply variable (M3) has a limited impact on inflation. Simultaneously, both GDP and loan interest rates substantially impact inflation. Conversely, money supply (M3), GDP, male unemployment, and loan interest rates simultaneously influence inflation in Asian countries. The study's findings indicate that unemployment does not exert a noteworthy detrimental impact on inflation, demonstrating the ineffectiveness of the Phillips curve for non-Asian nations. Each ASEAN member state implements diverse policies to manage and control the inflation rate. Hong Kong can enforce price monitoring measures to deter market manipulation. Vietnam could enhance its trade policy to alleviate the consequences of imported inflation. Korea can sustain interest rates at a moderate level. Indonesia can synchronize monetary and fiscal policies in order to manage inflation.